2022
DOI: 10.3389/fendo.2022.732731
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Serum Folate and Total Calcium and Magnesium Levels Before Ovarian Stimulation With Outcomes of Fresh In Vitro Fertilization Cycles in Normogonadotropic Women

Abstract: BackgroundWomen of reproductive age are recommended to consume folic acid and other supplements before conception and during pregnancy. We aimed to investigate the association of the serum folate and total magnesium (Mg) and calcium (Ca) levels before ovarian stimulation with the outcomes of assisted reproductive technology (ART) in normogonadotropic women.MethodsWe used a subanalysis of data obtained from a multicentre, randomized prospective study (NCT03088137). A total of 110 normogonadotropic, non-advanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
(66 reference statements)
0
6
0
1
Order By: Relevance
“…In T2D patients, some studies suggested that a Mg deficiency and iron metabolism are involved in the induction of hemolysis, which contributes to iron release [113]. Folic acid is an essential micronutrient for many physiological processes [115]. In an in vitro study in rats, added extracellular Mg and folic acid decreased the homocysteine-induced matrix metalloproteinase-2 (MMP-2), which plays an essential role in the formation and progression of atherosclerotic lesions secretion [116].…”
Section: Magnesium and Its Associationsmentioning
confidence: 99%
“…In T2D patients, some studies suggested that a Mg deficiency and iron metabolism are involved in the induction of hemolysis, which contributes to iron release [113]. Folic acid is an essential micronutrient for many physiological processes [115]. In an in vitro study in rats, added extracellular Mg and folic acid decreased the homocysteine-induced matrix metalloproteinase-2 (MMP-2), which plays an essential role in the formation and progression of atherosclerotic lesions secretion [116].…”
Section: Magnesium and Its Associationsmentioning
confidence: 99%
“…Serum folate level (≥33.0 ng/mL) and a lower Ca/Mg ratio were associated with worse assisted reproductive technology (ART) outcomes in normogonadotropic women. A baseline lower Ca/Mg ratio (<4.55) was associated with worse clinical ART outcomes in a dose-dependent manner [ 143 ].…”
Section: Discussionmentioning
confidence: 99%
“…This putative feature has been supported by a recent animal study, which demonstrates that while 200 pM of cyanocobalamin supplement during in vitro oocyte maturation results in a higher likelihood of blastulation, and lower preimplantation development arrest and degeneration, doses as high as 300 or 500 pM undermine embryo developmental potential and increase the probability of degeneration (11). For folate, although most researchers demonstrated a positive correlation of the serum folate level with reproductive outcomes (17, 18, 43), some showed an impaired outcome if the serum folate level is higher than 33.0 ng/mL (21). These biphasic patterns for vitamin B12 and folate may also exist in other conditions, such as coronary artery disease and fracture risk (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have attempted to validate the biological relevance of pre-conception B vitamins for female reproduction in couples under infertility treatments, but they have contradictory conclusions. While some show that supplementation with folate and vitamin B12 before oocyte retrieval may improve embryo quality, implantation potential, and live birth during IVF-ET treatment (16)(17)(18), others found no beneficial effects on pregnancy outcomes (19,20), or even reached an opposite association (21). Moreover, all published clinical studies exclusively focus on folate and vitamin B12, the two major vitamins related to the one-carbon metabolism pathway, with no examination of the clinical effects of other B vitamins during infertility treatment, despite their recommendation for general health.…”
Section: Introductionmentioning
confidence: 99%